A fully human monoclonal antibody targeting ckit is a potent inhibitor of pathological choroidal neovascularization in mice - Seo, Songyi; Kim, Koung Li; Yeo, Yeongju; Kim, Ryul I.; Jeong, Hayoung; Kim, Jin Ock; Song, Sun Hwa; An, Mi Jin; Kim, Jung Woong; Hong, Hye Kyoung; Ham, Min Hee; Woo, Se Joon; et al. (Pharmaceutics, 2021)
Stem cell factor (SCF) and its receptor, cKIT, are novel regulators of pathological neo-vascularization in the eye, which suggests that inhibition of SCF/cKIT signaling may be a novel pharmacological strategy for treating neovascular age-related macular degeneration (AMD). This study evaluated the therapeutic potential of a newly developed fully human monoclonal antibody targeting cKIT, NN2101, in a murine model of neovascular AMD. In hypoxic human endothelial cells, NN2101 substantially inhibited the SCF-induced increase in angiogenesis and activation of the cKIT signaling pathway. In a murine model of neovascular AMD, intravitreal injection of NN2101 substantially inhibited the SCF/cKIT-mediated choroidal neovascularization (CNV), with efficacy comparable to aflibercept, a vascular endothelial growth factor inhibitor. A combined intravitreal injection of NN2101 and aflibercept resulted in an additive therapeutic effect on CNV. NN2101 neither caused ocular toxicity nor interfered with the early retinal vascular development in mice. Ocular pharmacokinetic analysis in rabbits indicated that NN2101 demonstrated a pharmacokinetic profile suitable for intravitreal injection. These findings provide the first evidence of the potential use of the anti-cKIT blocking antibody, NN2101, as an alternative or additive therapeutic for the treatment of neovascular AMD.
Keywords: Age-related macular degeneration; Choroidal neovascularization; CKIT; Fully human monoclonal antibody; Stem cell factor